Data Resource: the National Pupil Database (NPD) - Matthew Alexander Jay; Louise Mc Grath-Lone; Ruth Gilbert (International Journal of Population Data Science, 2019)
Introduction The National Pupil Database (NPD) is a record-level administrative data resource curated by the UK government’s Department for Education that is used for funding purposes, school performance tables, policy making, and research.